2011
DOI: 10.1111/j.1741-2358.2011.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

The short‐term effects of various oral care methods in dependent elderly: comparison between toothbrushing, tongue cleaning with sponge brush and wiping on oral mucous membrane by chlorhexidine

Abstract: The short-term effects of various oral care methods in dependent elderly: comparison between toothbrushing, tongue cleaning with sponge brush and wiping on oral mucous membrane by chlorhexidine Objectives: To explore the short-term effects from toothbrushing, tongue cleaning with sponge brush and wiping on oral mucous membrane by chlorhexidine. Background: Numerous reports have been seen in recent years proving the effectiveness of mouth cleaning with a toothbrush for the prevention of respiratory infections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…A previous study conducted among the dependent elderly in Japan found that wiping oral mucosa with a sponge brush soaked in chlorhexidine decreased opportunistic infections in the pharyngeal region (p < 0.05). (14) Another consistent finding from a study in Brazil was that chlorhexidine-based treatment had the ability to remove oral biofilm in 60 geriatric patients. (20) In addition, the present study confirmed that daily application of chlorhexidine 0.2% solution is effective in reducing microbes in the oral cavity.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…A previous study conducted among the dependent elderly in Japan found that wiping oral mucosa with a sponge brush soaked in chlorhexidine decreased opportunistic infections in the pharyngeal region (p < 0.05). (14) Another consistent finding from a study in Brazil was that chlorhexidine-based treatment had the ability to remove oral biofilm in 60 geriatric patients. (20) In addition, the present study confirmed that daily application of chlorhexidine 0.2% solution is effective in reducing microbes in the oral cavity.…”
Section: Discussionmentioning
confidence: 73%
“…A similar study in Japan was also unable to provide data on the incidence of aspiration pneumonia. (14) The absence of aspiration pneumonia in our patients may have been due to the short-term effects of oral hyigene care over seven days and the small sample size. Previous research recommended having a study with a longer duration and higher number of patients, to possibly support the theory that effective oral care is an important contributing factor in the prevention of aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Aspiration of oral secretions is one of the most important aetiology of ventilator associated pneumonia [4,7,12,22,23,24]. Contaminated secretions of oral cavity collect above the endotracheal tube cuff and which can trickle down the trachea to lung along the cuff.…”
Section: Discussionmentioning
confidence: 99%